The respiratory microbiome and innate immunity in asthma - Huang, Yvonne J (Current opinion in pulmonary medicine, 2015)
The purpose of this study is to summarize recent studies of the lower respiratory microbiome in asthma, the role of innate immunity in asthma and strategies to understand complex microbiome-immune interactions in asthma. Recent evidence indicates that the composition of lower respiratory microbiota in asthmatic individuals, across a spectrum of disease severity, is altered compared with healthy individuals. Attributes of this altered airway microbiome have been linked to clinical and inflammatory features of asthma. The importance of innate immune cells and mucosal defense systems in asthma is increasingly appreciated and may be dysregulated in the disease. Interactions between the respiratory microbiome and innate mucosal immunity in asthma are complex and a challenge to dissect. Multiple avenues of investigation, leveraging a variety of methodologies, will need to be pursued to understand functional relationships to clinical and inflammatory phenotypes seen in asthma.